Evidence for trans-generational immune priming against Vibrio splendidus in the oyster Crassostrea gigas - Song, Xiaorui; Wang, Weilin; Dong, Miren; Liu, Chang; Yang, Chuanyan; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2025)
Cumulative evidence have demonstrated the occurrence of trans-generational immune priming (TGIP) in invertebrates; however, the detailed substances transferred, and the mechanism of this transmission remain unclear. In the present study, we first tested TGIP in the offspring of Crassostrea gigas after parental challenge with Vibrio splendidus during the spawning season. In the maternal oyster primed with V. splendidus, the enzyme activities (lysozyme and SOD), NO level, the expression of immune genes (CgTLR2, CgMACPF, and CgFBG), as well as the antibacterial activities were significantly enhanced in the eggs of V. splendidus-primed female oysters, indicating that V. splendidus stimulation promoted the immunity tendentiously transferred to eggs during the spawning season. After fertilization, the enzyme activities of CAT, lysozyme, and SOD were significantly enhanced in the maternal primed group [mVs-Sw (M)] during early oyster ontogeny, whereas there were no detectable differences between the control group (nSw-Sw (N)) and paternal primed group [pVs-Sw (P)]. However, the expression of immune genes (CgGalectin, CgMyd88, and CgLBP) increased in the parental primed groups (mVs-Sw (M) and pVs-Sw (P)). After the larval offspring were exposed to the secondary V. splendidus stimulation, the mortality rates in the parental TGIP groups [mVs-Vs (M1) and pVs-Vs (P1)] were significantly lower, while the hatching rates were significantly higher than those in the nSw-Vs (N1), confirming that parents’ immunological experience enhanced their offspring survival rates as well as their resistance to pathogen infection. Transcriptome data revealed that differentially expressed genes were enriched in immunity, signal transduction, energy metabolism, and development in the parental TGIP groups. Notably, the expression levels of the three DNMTs were all significantly upregulated during early ontogeny in the maternal primed groups [mVs-Sw (M)], but sharply increased after entering the D-veliger larvae in the paternal primed group (pVs-Sw (P)), suggesting the potential regulation of DNA methylation during oyster TGIP. Moreover, the expression of E3 ligases (CgWWP1, CgSmurf2, CgNedd4, and CgMarch5) was significantly increased at the D-veliger and early umbo larval stages after V. splendidus stimulation, indicating their immune role during oyster ontogeny. These results are the first to show evidence of bacteria-induced TGIP and its potential mechanisms in mollusks.